+0  
 
0
284
1
avatar

2x=10-y y-x=-2

Guest Nov 10, 2014

Best Answer 

 #1
avatar+17728 
+5

2x  =  10 - y

y - x  =  -2     --->   (solve for y)   --->   y  =  x - 2

Replace this into the other equation:  2x  =  10 - (x - 2)

                (distribute)                           2x  =  10 - x + 2 

                (add x to both sides)            3x  =  12

                (divide by 3)                           x  =  4

Replace this into the equation  y  =  x - 2     --->     y  =  4 - 2     --->     y  =  2

geno3141  Nov 12, 2014
Sort: 

1+0 Answers

 #1
avatar+17728 
+5
Best Answer

2x  =  10 - y

y - x  =  -2     --->   (solve for y)   --->   y  =  x - 2

Replace this into the other equation:  2x  =  10 - (x - 2)

                (distribute)                           2x  =  10 - x + 2 

                (add x to both sides)            3x  =  12

                (divide by 3)                           x  =  4

Replace this into the equation  y  =  x - 2     --->     y  =  4 - 2     --->     y  =  2

geno3141  Nov 12, 2014

20 Online Users

avatar
avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy